Influence of ion-neutral collisional frequency and Kappa spectral index on dynamics of nonlinear ion-acoustic waves in superthermal plasmas - M. Mehdipoor (مجله علوم و فنون هسته‌ای, 2021)
The present work investigates the propagation of nonlinear ion-acoustic waves in a collisional plasma with superthermal electrons and a Kappa distribution function. Considering the basic fluid equations and the ion-neutral collisions, a modified nonlinear Korteweg-de Vries (K-dV) equation is derived using the reductive perturbation method. It was found that only compressive ion-acoustic solitary waves can be propagated in this model. Also, the numerical results show that ion-neutral collisions have significant effects on solitary wave structures. In other words, the amplitude (width) of the ion-acoustic solitons decreases (increases) with increasing the ion-neutral collision frequency. Moreover, the present plasma model has also studied the effects of the spectral index of superthermal electrons and ion temperature on the ion-acoustic solitons